Comparative study of dose distributions and cell survival fractions for 1H, 4He, 12C and 16O beams using Geant4 and Microdosimetric Kinetic model. (31st March 2015) - Burigo, Lucas; Pshenichnov, Igor; Mishustin, Igor; Bleicher, Marcus
Abstract: Depth and radial dose profiles for therapeutic 1 H, 4 He, 12 C and 16 O beams are calculated using the Geant4-based Monte Carlo model for Heavy-Ion Therapy (MCHIT). 4 He and 16 O ions are presented as alternative options to 1 H and 12 C broadly used for ion-beam cancer therapy. Biological dose profiles and survival fractions of cells are estimated using the modified Microdosimetric Kinetic model. Depth distributions of cell survival of healthy tissues, assuming 10% and 50% survival of tumor cells, are calculated for 6 cm SOBPs at two tumor depths and for different tissues radiosensitivities. It is found that the optimal ion choice depends on (i) depth of the tumor, (ii) dose levels and (iii) the contrast of radiosensitivities of tumor and surrounding healthy tissues. Our results indicate that 12 C and 16 O ions are more appropriate to spare healthy tissues in the case of a more radioresistant tumor at moderate depths. On the other hand, a sensitive tumor surrounded by more resistant tissues can be better treated with 1 H and 4 He ions. In general, 4 He beam is found to be a good candidate for therapy. It better spares healthy tissues in all considered cases compared to 1 H. Besides, the dose conformation is improved for deep-seated tumors compared to 1 H, and the damage to surrounding healthy tissues is reduced compared to heavier ions due to the lower impact of nuclear fragmentation. No definite advantages of 16 O with respect to 12 C ions are found in this study.